The level of the functional movement screen among traditional dancers - A. Maniveloo, Segar; Abdullah, Borhannudin; Samsudin, Shamsulariffin (Canadian Center of Science and Education, 2021)
Movement assessments are commonly used to assess athlete’s risk of injury as well as basic and specific skill movement patterns; however, dance is identified to be differing from sports because the average dancer’s training load is higher than the athletes. This study aims to identify the difference in the Functional Movement Screen (FMS) level among traditional dancers in Malaysia. A quasi-experimental study design was adopted, which involved 66 dancers (M = 33; F = 33). The study comprised traditional dancers from three ethnic backgrounds, namely, Malay, Chinese and Indian. The descriptive analysis described the level of the dancers’ FMS, as follows: Malay (M = 16.18, SD = 2.062), Chinese (M = 18.50, SD = 1.102), Indian (M = 18.23, SD = 1.445). The ANOVA analysis found a significant difference in the FMS scores among all three groups of dancers, F (2,63) = 14.026, p >.000. The deep squat, hurdle step, shoulder mobility, active straight leg raise and trunk stability tests for push-up indicated a significant difference, whereas the inline lunges test and rotational stability tests showed no significance difference. However, the Post Hoc analysis showed no significant difference between the Chinese and Indian dancers. It can be concluded that there is a difference in FMS scores between Malay, Chinese and Indian dancers. FMS may be a useful tool to help identify dancers about the risk of injury and improve their movement quality.